Actual knowledge. (19th November 2021) - Phillips, Jonathan; Buckwalter, Wesley; Cushman, Fiery; Friedman, Ori; Martin, Alia; Turri, John; Santos, Laurie; Knobe, Joshua
Abstract: This response argues that when you represent others as knowing something, you represent their mind as being related to the actual world. This feature of knowledge explains the limits of knowledge attribution, how knowledge differs from belief, and why knowledge underwrites learning from others. We hope this vision for how knowledge works spurs a new era in theory of mind research.